SISTEM INFORMASI PENCATATAN KAS MASJID BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL (STUDI KASUS: MASJID AL-AQSHA TOLOTONGGA) - Nurfadilah; Syarifuddin; Dahlan (LPPM Universitas Abdurrab, 2026)
Manual financial management in mosques causes various problems, such as recording errors, delayed data recapitulation, and a lack of financial transparency for the congregation. This study aims to develop a Website-Based Mosque Cash Recording Information System (Case Study: Masjid Al-Aqsha Tolotongga) to improve the effectiveness, efficiency, and transparency of mosque financial management. The system was developed using the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and maintenance, using PHP as the programming language and MySQL as the database. The resulting system has six main features: cash income recording, cash expenditure recording, financial reporting, mosque activity management, announcements, and mosque profile. Black Box Testing results show that all system features function properly and are valid according to user needs. This system replaces manual recording with a digital-based system, enabling secure data storage, automatic report generation, and transparent access to financial information for the congregation through the website.